DIFERENÇAS ENTRE AS ESCALAS REGIONAL E LOCAL NA APLICAÇÃO DA ABORDAGEM MULTICRITÉRIO DA VULNERABILIDADE COSTEIRA: ESTUDO DE CASO NO LITORAL SUL DO ESPÍRITO SANTO - Filgueiras, Gilberto Daniel Lima (2020)
In the last few decades, issues related to coastal vulnerability have been important along the coasts of around the world, due to climate issues, rising sea levels and urban expansion over these regions. It is necessary to understand the degree of coastal